Am Empirical Examination of Deviations from the Laws of One Price Using West German Data - Beverly J. Lapham (Queen's University, Department of Economics, 1990)
Monthly West German producer, export, and import price indices are examined to investigate relationships among international prices. The data provides evidence of highly persistent time-varying deviations in the Law of One Price both across countries by a single producer and within a country by different international producers. The size and persistence of the deviations exhibits considerable variation across the industries studied. The time-varying deviations documented in this work appear to be much larger than what can be explained by variable tariffs and transport costs. Given the persistence of deviations, it is argued that theoretical models which seek to explain properties of international price data must be inherently dynamic.
Keywords: 330